Assessment of the learning process through the Maternal and Child Nursing Specialists health care practice - Norma Mur Villar; Miriam Iglesias León; María José Aguilar Cordero (Medisur)
The curriculum of the Maternal and Child Nursing Specialty is aimed to prepare professionals with theoretical and practical training that enables them to assume the responsibility of the health care of mothers and children as well as to contribute to the training of nurses at different levels. This study has been conducted in the province of Cienfuegos in order to determine the regularities that have been taking place in the learning process through the health care practice and to enable, if it is necessary, a change in the professional performance. As final considerations we have the inadequacies in the learning process as to the integration of health care problems in the formation of graduates of this specialty, according to the new missions of the Medical University and the health services in the area of maternal and child care.